Non-orthogonal multiple-access system SC-FDMA-IDMA with iterative block equalization - De-liang LIU; Qiang HUANG; Da-zhuan XU (Tongxin xuebao)
As a new non-orthogonal multiple-access scheme, SC-FDMA-IDMA combines two technologies of SC-FDMA and IDMA together. This combination makes SC-FDMA-IDMA have the probability to inherit different advantages of these two technologies such as large system capacity, low peak-to-average power ratio (PAPR) and simple multiuser de-tection. However, because SC-FDMA for the transmission of different users' signal is a special form of single carrier modulation, the system performance may degrade quickly when the frequency selectivity of channel is serious. So the it-erative block decision feedback equalization (IB-DFE) algorithm applied to the SC-FDMA-IDMA system is derived in order to enhance the ability of anti-frequency selective fading. Simulation results show that comparing with the sin-gle-user SC-FDMA system with high-order modulation, the multiuser SC-FDMA-IDMA system with low-order modula-tion has great performance improvement after adopting the IB-DFE algorithm on condition that these two systems have the same transmission efficiency.